Prevalence, etiology, and transmission of fibropapillomatosis in Olive Ridley turtles at a mass-nesting colony in the Mexican Pacific - Elizabeth Labastida-Estrada; Karina Marisol Lugo-Trejo; Valentina Islas-Villanueva; Francisco Benítez-Villalobos; Federico Alberto Abreu-Grobois; Alejandro Oceguera-Figueroa (PLoS ONE, 2026)
Fibropapillomatosis (FP) is a widespread disease in sea turtles characterized by the development of internal and external tumors that hinder physiological and general functions. Chelonid alphaherpesvirus 5 (ChAHV5) is recognized as the causative agent and has been studied and characterized worldwide. Here, we evaluated the prevalence and severity of FP in olive ridley females ( Lepidochelys olivacea ) during the mass-nesting season from July 2022 to January 2023 at Playa Escobilla, Oaxaca, on the Mexican Pacific coast. Using fragments of the capsid protein (UL18) and DNA polymerase (UL30) genes, we assessed the molecular detection of viral DNA in tumors and healthy tissues from FP-affected and apparently healthy females. To explore the potential role of the marine leech Ozobranchus branchiatus as a vector, we also screened leeches collected from both FP-affected and healthy turtles for viral DNA. Additionally, we identified ChAHV5 genetic variants from UL18 and UL30 sequences obtained from turtles and leeches. The estimated FP prevalence was 1.05%. Among the 62 FP-affected females, 82% were classified as mild, 13% as moderate, and 5% as severe. Molecular detection using the UL30 marker achieved a 100% detection rate in FP-affected turtles and 91% in apparently healthy individuals. In contrast, viral DNA was detected in only 6% of the analyzed leeches. Based on UL18, we identified a novel variant exclusive to olive ridley turtles (UL18_haplotype 3), while six UL30 variants were recorded, with UL30_Var01 being the most abundant and widely distributed in the Pacific. The low detection rate of ChAHV5 in leeches does not support their role as vectors. Our findings provide critical evidence of latent viral presence and highlight the need for integrating molecular surveillance in nesting sites to improve our understanding of FP dynamics and its potential impact on sea turtle conservation.